2018
DOI: 10.1016/j.ijsu.2018.05.737
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of incidental parathyroidectomy after total thyroidectomy: The effect on hypocalcemia. A retrospective cohort study

Abstract: Our results indicate that patients with certain preoperative findings such as larger thyroid dimensions, diagnosis of malignancy and especially tumor >10 mm, extrathyroidal extension, and lymph node metastasis are at higher risk of IP and postoperative symptomatic hypocalcemia and these patients should be adequately informed and treated. Α meticulous intraoperative identification and the preservation of all parathyroid glands results in lower incidence of IP and postoperative hypocalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 23 publications
5
38
0
Order By: Relevance
“…Finding a parathyroid gland in postoperative thyroidectomy specimen without any intention to do parathyroidecomy is known as incidental parathyroidectomy (IP). The incidence ranges between 6.4% and 31.1% [5][6][7][8][9][10][11]. Over the past decades, standardization of the thyroidectomy technique and advances in perioperative management have led to significant reduction in the overall morbidity [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding a parathyroid gland in postoperative thyroidectomy specimen without any intention to do parathyroidecomy is known as incidental parathyroidectomy (IP). The incidence ranges between 6.4% and 31.1% [5][6][7][8][9][10][11]. Over the past decades, standardization of the thyroidectomy technique and advances in perioperative management have led to significant reduction in the overall morbidity [5].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence ranges between 6.4% and 31.1% [5][6][7][8][9][10][11]. Over the past decades, standardization of the thyroidectomy technique and advances in perioperative management have led to significant reduction in the overall morbidity [5]. Although IP is considered a minor finding in final histopathology and not a life-threatening complication of thyroid surgery, it is important for the thyroid surgeon to be able to identify factors that increase the risk for IP during thyroidectomy and exercise appropriate caution in those patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that inadvertent parathyroidectomy is approximately 18% during thyroid surgery, while patients experience temporary hypocalcemia (28.9%‐30.7%) and permanent hypocalcemia (1.6%‐9.6%) after thyroid surgery .…”
Section: Introductionmentioning
confidence: 89%
“…The primary treatment for thyroid cancer is removal of the thyroid tissue containing the lesions, a procedure called thyroidectomy. [5][6][7] There is also economic burden due to the need to take calcium and vitamin D supplements. [1,2] However, it is difficult to clearly distinguish the parathyroid glands from neighboring tissues because they are similar in color to the naked eye, the surgeon may lack the experience and some patients have a lot of fat tissue around the thyroid.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] The incidence of iatrogenic injury of parathyroid glands is 0.6% to 9.2% in all thyroid surgeries. [5][6][7] There is also economic burden due to the need to take calcium and vitamin D supplements.…”
Section: Introductionmentioning
confidence: 99%